2020
DOI: 10.1111/ijfs.14917
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic Noni (Morinda citrifolia L.) leaf extract dechlorophyllised using sedimentation process: Antioxidant, antibacterial properties and efficacy in extending the shelf‐life of striped catfish slices

Abstract: The antimicrobial and antioxidant properties of ethanolic noni leaf extract were improved in the top fraction after sedimentation at 4 °C for 24 h

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…It was postulated that the higher TPC obtained in the MECLE sample extracted in 70% ethanol might have migrated inside the cashew leaf cells and washed out along with the cell matrix containing both polar and nonpolar phenolic compounds. The TPC of different extracts from guava leaves, custard apple leaves, and noni leaves showed a higher content of phenolic compounds extracted from mature leaves in aqueous ethanol [ 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was postulated that the higher TPC obtained in the MECLE sample extracted in 70% ethanol might have migrated inside the cashew leaf cells and washed out along with the cell matrix containing both polar and nonpolar phenolic compounds. The TPC of different extracts from guava leaves, custard apple leaves, and noni leaves showed a higher content of phenolic compounds extracted from mature leaves in aqueous ethanol [ 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…MIC was in the range of 64–256 µg mL −1 . This could be related to the high resistivity of GPB towards antibacterial agent mediated by the differences in their cell wall compositions as compared to GNB (Olatunde et al ., 2020a, 2020d). Irrespective of the bacteria, PEF‐CALE showed higher bacteria inhibitory properties than CALE.…”
Section: Resultsmentioning
confidence: 99%
“…This might be associated with the higher TPC and lower TChC in the former as compared to the latter (Table 1). The improved antibacterial properties were recorded for ethanolic guave leaf and noni leaf extracts after chlorophyll removal when compared to the control (without chlorophyll removal) (Olatunde et al ., 2020a, 2020c). The result indicated that the components in PEF‐CALE exhibited higher ability in inhibiting microorganisms than those present in CALE.…”
Section: Resultsmentioning
confidence: 99%
“…Olatunde, Benjakul, and Huda, et al. (2020b) and Olatunde, Della Tan, et al. (2020) found that dechlorophyllization of guava and noni leaf extract retarded the growth of gram‐negative Pseudomonas count and hydrogen sulfide‐producing bacteria (HSPB) and total viable count in FFP during refrigerated storage.…”
Section: Application Of Antimicrobials From Natural Sources For Ffp P...mentioning
confidence: 99%
“…Findings suggested that mint extracts had higher microbial inhibition as compared to citrus extracts. Olatunde, Benjakul, and Huda, et al (2020b) and Olatunde, Della Tan, et al (2020) found that dechlorophyllization of guava and noni leaf extract retarded the growth of gram-negative Pseudomonas count and hydrogen sulfide-producing bacteria (HSPB) and total viable count in FFP during refrigerated storage. Also, the ethanolic coconut husk extract was proven to inactivate the microorganism by damaging the cell wall.…”
Section: Plant Extractsmentioning
confidence: 99%